From the Eurozone Debt Crisis to the Alternative for Germany - Conrad, Maximilian (Frontiers in Political Science, 2020)
The sudden rise and subsequent radicalization of the “Alternative for Germany” (AfD) has been one of the politically most important consequences of the Eurozone debt crisis in Germany, both in relation to domestic politics and in the broader context of European-level right-wing populism. While initially founded as a single-issue party in opposition to Angela Merkel’s claim that there was no alternative to saving the common currency, the party quickly turned increasingly right-wing populist and xenophobic, not least in the wake of the 2015-2016 “refugee crisis”. This article traces the causal mechanisms underlying the rise and subsequent radicalization of the Alternative for Germany, spelling out the respective importance, but also the drawbacks, of the twin windows of opportunity presented by the Eurozone debt crisis and the refugee crisis. In addition, the paper draws particular attention to the ways in which the public claims-making of its key figures reflects the party’s overall development, i.e. from a soft Euroskeptic party aiming to dissolve the Eurozone to a conventional populist radical right party. Key figures highlighting this development include Bernd Lucke, Frauke Petry and Alexander Gauland, but certainly also extreme voices such as Björn Höcke.